2014
DOI: 10.1155/2014/125707
|View full text |Cite
|
Sign up to set email alerts
|

Problem Based Learning in Nursing Education

Abstract: Background. McMaster University first introduced Problem Based Learning (PBL) in the mid 1960s. However, measuring the relationship between PBL for undergraduate nursing programs and students test performance has not yet been assessed in the USA. Purpose. The main purpose of this paper is to describe the effectiveness of PBL on senior student test performance on content related to PBL in a BSN program. Diabetes mellitus and renal insufficiency were taught by traditional lecture format in the previous years. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…PBL was adopted because of the school's extensive course content, using lecturing as the main teaching method and the evidenced incongruity between educational and evaluation objectives [3]. According to [4], most medical educators have adopted PBL as the educational and philosophical basis of their curricula.…”
Section: Historical Background Of Pblmentioning
confidence: 99%
“…PBL was adopted because of the school's extensive course content, using lecturing as the main teaching method and the evidenced incongruity between educational and evaluation objectives [3]. According to [4], most medical educators have adopted PBL as the educational and philosophical basis of their curricula.…”
Section: Historical Background Of Pblmentioning
confidence: 99%
“…Several studies have demonstrated that CE programmes should involve robust design and teaching methods that integrate theoretical, practical and experiential learning, potentially resulting in improvements in professional practice, patient care and health outcomes (Duff, ; Gallagher, ; Zurmehly, ). Interactive learning strategies, such as scenario‐based learning and simulation, in addition to lecture and continuous feedback, are effective education approaches for behaviour change and sustainability (Duff, ; Wax et al, ; Zhang, ). None of the studies identified reported using interactive education techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Although the assumption guiding CBL requires that students learning is facilitated with a scenario structured on real life issues, [29,30,34] the integration of lectures in CBL program is supported in the literature. [49] Concepts that are difficult and require more fundamental knowledge, retrieving, and comprehension should be taught in different formats including lecture, seminar, and case study to ensure mastery of the content knowledge by the students. [49] Currently, a hybrid form of CBL where lectures are integrated with CBL is provided in the study setting.…”
Section: Discussionmentioning
confidence: 99%
“…[49] Concepts that are difficult and require more fundamental knowledge, retrieving, and comprehension should be taught in different formats including lecture, seminar, and case study to ensure mastery of the content knowledge by the students. [49] Currently, a hybrid form of CBL where lectures are integrated with CBL is provided in the study setting.…”
Section: Discussionmentioning
confidence: 99%